Solvent-free synthesis of highly dispersed zinc-doped porous carbons as efficient dibenzothiophene adsorbents - Ping Lu; Zhenhua Sun; Xinrong Ke; Changshen Ye; Zhixian Huang; Ting Qiu (Green Energy & Environment)
Designing efficient adsorbents for the deep removal of refractory dibenzothiophene (DBT) from fuel oil is vital for addressing environmental issues such as acid rain. Herein, zinc gluconate and urea-derived porous carbons SF-ZnNC-T (T represents the carbonization temperature) were synthesized without solvents. Through a temperature-controlled process of “melting the zinc gluconate and urea mixture, forming H-bonded polymers, and carbonizing the polymers,” the optimal carbon, SF-ZnNC-900, was obtained with a large surface area (2280 m2 g−1), highly dispersed Zn sites, and hierarchical pore structures. Consequently, SF-ZnNC-900 demonstrated significantly higher DBT adsorption capacity of 43.2 mg S g−1, compared to just 4.3 mg S g−1 for the precursor. It also demonstrated good reusability, fast adsorption rate, and the ability for ultra-deep desulfurization. The superior DBT adsorption performance resulted from the evaporation of residual zinc species, which generated abundant mesopores that facilitated DBT transformation, as well as the formation of Zn-Nx sites that strengthened the host-guest interaction (ΔE = −1.466 eV). The solvent-free synthesized highly dispersed Zn-doped carbon shows great potential for producing sulfur-free fuel oil and for designing metal-loaded carbon adsorbents.